Lung cancer stigma and depression: Validation of the Lung Cancer Stigma Inventory. Issue 5 (16th April 2019) - Ostroff, Jamie S.; Riley, Kristen E.; Shen, Megan J.; Atkinson, Thomas M.; Williamson, Timothy J.; Hamann, Heidi A.
Abstract: Objective: In an effort to provide further evidence for the validity of the Lung Cancer Stigma Inventory (LCSI), this paper examined group differences in lung cancer stigma for patients who report clinically significant depressive symptoms and established a suggested scoring benchmark to identify patients with clinically meaningful levels of lung cancer stigma. Methods: Patients (N = 231) who were diagnosed with lung cancer and treated within the past 12 months at one of two National Cancer Institute (NCI)‐designated Cancer Centers located in the northeast and southern parts of the United States completed a single battery of questionnaires examining lung cancer stigma and depressed mood. Group differences, bivariate correlations, and receiver operating characteristic (ROC) analyses were conducted. Results: Slightly more than a third of patients (35.9%) reported an elevated level of depression. There was a significant correlation ( r =  0.44) between lung cancer stigma and depressive mood. The ROC curve analysis indicated an area under curve (AUC) of 0.71. A LCSI cutoff score of 37.5 yielded the optimal ratio of sensitivity (0.93) to specificity (0.70) for identifying patients with clinically meaningful lung cancer stigma. Conclusions: Consistent with prior work, lung cancer stigma, as measured by the LCSI, was found to be moderately associated with depressed mood. Clinical investigators may use an LCSI total score above 37.5 (ie, greater than or equal to 38 on the LCSI scale of integer scores) as a clinical threshold for identifying patients who may be experiencing clinically meaningful stigma and may benefit from stigma‐reducing interventions.